Faktor Penentu Perawat sehat di Rumah Sakit - Endang Sudjiati; Hanny Handiyani; Kuntarti Kuntarti; La Ode Abdul Rahman; Cori Tri Suryani (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2023)
Healthy behavior carried out by nurses often does not produce good results due to several factors. The risks that arise due to not behaving healthy nurses can reduce the health condition of nurses and the quality of service. The purpose of this study was to identify the factors that can influence the behavior of healthy nurses. The research method used a cross-sectional design to 356 nurses at the General Hospital in Jakarta. The results of the analysis showed that there was a significant relationship between age 35 years (p = 0.038) and education D3 Nursing/Midwifery (p = 0.034) with healthy nurse behavior. In multivariate analysis, the most influential variables on the behavior of healthy nurses were physical activity (p<0.05; OR = 4.760, 95%CI), spiritual (p=0.211; OR = 1.456, 95%CI) and stress management (p< 0.05; OR = 4.549, 95%CI). Recommendations to improve the behavior of healthy nurses by making healthy nurse programs on a regular basis.